2010
DOI: 10.1016/j.proeng.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A review of CAA for fan duct propagation and radiation, with application to liner optimisation

Abstract: This article reviews the application of Computational Aero-Acoustics (CAA) to the prediction of acoustic propagation in turbofan ducts. The challenge of resolving the radiated sound field for realistic nacelle geometries is discussed and evidence is presented to indicate that current CAA is able to represent the effect of in-duct liners on far-field measured rig and engine data. Two approaches are presented for incorporating CAA predictions within liner optimisation schemes for a turbofan intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
(60 reference statements)
0
7
0
1
Order By: Relevance
“…The linearised Navier-Stokes equations may also support vorticity and entropy waves but these are not of primary interest here. A pragmatic alternative frequently employed has been to include the boundary layer in the impedance model and to assume that the flow is potential [2]. This is computational much lighter and is attractive particularly for inverse searches of liner impedance values from experimental data or large-scale design optimisations.…”
Section: A Wem-based Methodology For Computing the Propagation In A Lmentioning
confidence: 99%
See 2 more Smart Citations
“…The linearised Navier-Stokes equations may also support vorticity and entropy waves but these are not of primary interest here. A pragmatic alternative frequently employed has been to include the boundary layer in the impedance model and to assume that the flow is potential [2]. This is computational much lighter and is attractive particularly for inverse searches of liner impedance values from experimental data or large-scale design optimisations.…”
Section: A Wem-based Methodology For Computing the Propagation In A Lmentioning
confidence: 99%
“…The Myers boundary condition has been widely used to achieve numerical predictions of lined duct propagation [2,18], which are considered to be sufficiently accurate for engineering applications. However, there have been a number of studies in recent years, which have identified problems with Myers condition resulting from the modelling assumptions.…”
Section: A Wem-based Methodology For Computing the Propagation In A Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications can be found in turbofan/turbomachinery (74)(75)(76) and environment control device (77) noise predictions. A more comprehensive review in this respect can be found in references (78)(79)(80)(81) .…”
Section: Noise Emissionmentioning
confidence: 99%
“…Sound generated by the rotor wake OGV interaction propagates through a swirling sheared flow between the rotor and OGV. Fan noise propagates through the flow in the engine inlet and in the bypass duct and is attenuated by the acoustic liners on the walls of these ducts [122]. As the engine size has grown with rated power and to accommodate higher bypass ratio, the length of the inlet duct has shrunk and thus the opportunity for attenuation by liners.…”
Section: (Iv) Fan and Turbomachinery Noisementioning
confidence: 99%